Rethinking Alternative Education Accountability Indicators: A Multilevel and Contextual Perspective. Issue 4 (9th May 2021) - Newton, Xiaoxia A; Lohmeier, Jill Hendrickson; Thompson, Shanna Rose; Oh, Bangsil; Dmello, Jared R; Trainor, Amanda
Abstract : School performance indicators commonly used for school accountability purposes (e.g., student attendance, achievement on standardized test scores, graduation rates) do not adequately reflect student progress in an alternative education context (Brewer et al., 2001; De Velasco & Gonzales, 2017; Rumberger & Palardy, 2005; Warren, 2016). Although proposals of alternative accountability indicators exist, these proposals rarely consider contextual indicators that are important for understanding the academic outcomes of students attending alternative schools. In this study, we argue for a multilevel and contextual perspective on alternative school accountability system just as some scholars in the education and health sectors have argued for a multilevel social–ecological framework for understanding individuals in context (Bronfenbrenner, 1977; Golden & Earp, 2012; Lemieux‐Charles et al., 2003). We present our conceptualization (i.e., Multi‐level Contextual School Accountability Framework) of what a comprehensive and fair accountability system might look like, based on reviews of existing literature and our evaluation of an alternative school's effort to transform into a full‐servicecommunity school.